Model performance (AUC) - dataframe - Radinger, Johannes; Wolter, Christian; Kail, Jochem (Dryad Digital Repository, 2015)
R-dataframe storing the model performance (AUC) of the single models for 13 species, four modelled distance classes, assessed vs. measured variables and with/without topological variables. The dataframe is stored as R object in the *.rds format and can be loaded with the R command readRDS().